Stagnation of Islamic Banking In Indonesia: Analysis Factors And Solutions - Ratno Agriyanto, Ratno Agriyanto; Ali Murtadho; Nasrul Fahmi Zaki Fuadi; Muhammad Saifullah; Siti Mujibatun; Abdulhamid Ali Abukil (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to shed light on why there hasn't been a noticeable rise in Islamic banks during the past three decades of their existence. Data were gathered for this qualitative study through observation, interviews, and documentation studies. The study's findings demonstrate that the growth of Islamic banks has slowed, as evidenced by their low market share, declining financing deposit ratio (FDR), and declining return on assets (ROA). The expansion of the Islamic Banking staff network and offices has also slowed down. Islamic banking's initial reasons for stagnation include its subpar performance in carrying out social tasks, specifically the collecting and distribution of cash. The second requirement is the capacity to apply sharia principles to every banking activity. The three Arabic term labels on the goods offered by Islamic Banking continue to cause confusion in the community. Fourth, judicial disputes unrelated to banking include entities and people associated with sharia designations, which have an effect on public confidence. To change the stagnation of Islamic banks, strategic steps including expanding their social role are required.